Making Covid-19 vaccination mandatory : a discussion from the perspective of beauchamp & childress principle and jurisprudence - Elle Natasha Abdul Razak,; Farah Nursabrina Ahamad Kamal,; Althabhawi, Nabeel Mahdi (Fakulti Undang-Undang, Universiti Kebangsaan Malaysia, 2022)
Known as COVID-19, a respiratory illness caused by the SARS-CoV-2 coronavirus was discovered in December 2019 and the vaccines provided are being hailed as the answer to bringing the world back to normal. As Delta variant together with Omicron infections have surged, and vaccinations have slowed down, this has prompted governments to implement COVID-19 injections mandatory for health workers and other groups at risk. Many countries have decided to make vaccinations mandatory to prevent serious harm to others in a similar community. However, individual rights and autonomy are threatened by this major decision as it has been argued that the consent of vaccination lies on each individual which has led to the issues of the right to bodily integrity. Even so, human life has been devastated by the COVID-19 pandemic, which poses a major threat to public health, food systems, as well as the world of work. The global pandemic has had a catastrophic effect on the economy and society. The governments have the authority to intervene if they are able to demonstrate that such intervention is necessary and appropriate to the accomplishment of another important objective. Mandatory vaccinations say, proponents of mandates, are an acceptable intrusion on an individual's freedom and autonomy in the particular circumstance of COVID-19. Such opinion has led to another issue concerning whether it is morally permissible to do so. The aspect of morality rests upon the four essences of the well-known medical ethics devised by Beauchamp and Childress along with one of the Jurisprudence theories which accepts morality as an essential component of law making, the Naturalism. With regards to the current events of Covid-19, the question of whether the vaccines should be mandated or not lies upon the perspective and debate from the medical views and regulations governing a society. This paper aims to analyze the connection between the Beauchamp and Childress principle and Jurisprudence to achieve conclusive findings and decisions concerning the need of making the Covid-19 vaccination mandatory for every individual.